Determinan Kepatuhan Minum Obat Tuberkulosis Di UPT Puskesmas Garoga Kecamatan Garoga Kabupaten Tapanuli Utara Tahun 2023 - Hutauruk, Ricardo; Manurung, Kesaktian; Hutajulu, Johansen; Nababan, Donal; E Sitorus, Mido (Journal of Pharmaceutical and Sciences, 2025)
Tuberculosis (TB) is a highly infectious disease caused by Mycobacterium tuberculosis, primarily affecting the lungs and transmitted through airborne droplets. As a global health concern, TB requires long-term treatment adherence to ensure successful outcomes. This study aimed to identify determinants of medication compliance among TB patients at the UPT Garoga Community Health Center, North Tapanuli Regency, in 2023. Using a cross-sectional design, data were collected from 42 patients through interviews and medical records. Variables analyzed included age, gender, education, occupation, knowledge, the role of health workers, and medication supervisors (PMO). Univariate, bivariate, and multivariate analyses were conducted to assess relationships between these factors and medication compliance. Results indicated significant associations between compliance and age (p = 0.001), gender (p = 0.006), education (p = 0.001), knowledge (p = 0.002), the role of health workers (p = 0.001), and PMO support (p = 0.002). However, no significant relationship was found between occupation and compliance (p = 0.036). These findings highlight the importance of patient education, health worker involvement, and family support in improving TB treatment adherence. The study underscores the need for targeted interventions to address these determinants and enhance treatment outcomes in TB patients.